"Are all things equal? Operational considerations in the integration of deemed employees into workplaces" - Otten, Rosita Joanne (University of the Witwatersrand, Johannesburg, 2022)
This research report is a policy-based study of the regulation of temporary employment services in South Africa. It is set against a contextual background of the development of Labour Brokers in South Africa as well as a contextual understanding of the regulation of temporary or atypical employees under International Labour Organisations Standards (ILO). The scope of this research is limited to only considerations of ILO Standards and does not consider a comparator of other countries. Future research could take it further in this regard to measure how Labour Brokers are offered labour law protections globally. This research report considers the development of labour law in South Africa and how the changes in the South Africa’s labour law policy have introduced mechanisms to afford and ensure greater protection of this vulnerable employee. The research reviews the recent legislative overhaul, in consideration of having the purpose to offering progressive protection to various atypical forms of employees and specifically a temporary employee who attains a deemed employment relationship status. The research aims to assess the extent to which the amendments to the South African labour legislative framework has been able to achieve its desired aims, by first considering how the provisions relating to temporary employment services, should be interpreted and applied. Secondly reviewing various operational considerations that impact the full integration of the deemed employee into the workplace in order to ensure on the whole not less favourable treatment and finally in having reviewed such operational considerations, assess and critique the impact these amendments have achieving protection of this vulnerable class of employee
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2022
Keywords: Temporary employment; Labour Brokers; South Africa; International Labour Organisations Standards (ILO); South Africa’s labour law policy; Employees; Deemed employees; UCTD; SDG-8: Decent work and economic growth